ET-11 ANALYSIS OF ANTI-GLIOMA EFFECT BY PROINFLAMMATORY CYTOKINES. (16th December 2019) - Adachi, Koji; Yamaguchi, Fumio; Higuchi, Tadashi; Takahashi, Hirosi; Morita, Akio
Abstract: OBJECT: Antiglioma activity of proinflammatory cytokines, (TNF-alpha, IL-2, IL-12 related cytokines, IL-18, IL-32) are analyzed. Most effective combinations of cytokines are investigated. MATERIAL & METHOD: Antitumor activity against U373MG, U87MG were measured by co-culture with PBMC and by nude mouse subcutaneous transplantation model. Cytokine receptors on PBMC and glioma cell lines were examined by IHC and mRNA expression. Anti-tumor activity was measured by local injection and systemic administration of proinflammatory cytokines. Cell cycle alteration and expression of apoptosis-related genes after cytokine administration was analyzed. Serum concentraion of cytokines is measured by ELISA. RESULT: Cytokine receptors were not expressed on glioma cells but were present on intratmoral mononuclear cells. Anti-tumor activity against transplanted tumor is strongly observed by focal administration. Expression of apoptosis-related genes were augmented. IFN-gamma was strongly induced by TNF-alpha, IL-2 and IL-12 administration. IFN-gamma, IL-17, TNF-alpha were also induced. IL-27 and IL-32 per se did not induce IFN-gamma. Simultaneous IL-27 and IL-12 induced strong IFN-gamma induction. Anti-glioma activity of IL-12 and IL-23 were higher than the same dose of exogenous IFN-gamma. IFN-gamma, IL-2 plus IL-12 in U373MG, and IFN-gamma, IL-2 plus IL-18 in U87MG seemed to be the best combination. CONCLUSIONS: Strong anti-glioma activity was induced by proinflammatory cytokines at least partially through IFN-gamma. There may be another factors. IL-2 and IL-23 showed anti-tumor activity through IFN-gamma, IL-17, TNF-alpha. IFN-gamma + IL-2 + IL-12/-18 seems to be the best combination.